Role of IMRT/VMAT-Based Dose and Volume Parameters in Predicting 5-Year Local Control and Survival in Nasopharyngeal Cancer Patients - Iacovelli, Nicola Alessandro; Cicchetti, Alessandro; Cavallo, Anna; Alfieri, Salvatore; Locati, Laura; Ivaldi, Eliana; Ingargiola, Rossana; Romanello, Domenico A.; Bossi, Paolo; Cavalieri, Stefano; Tenconi, Chiara; Meroni, Silvia; et al. (Frontiers in Oncology, 2020)
Objective: This study aimed to look into the relationship between intensity-modulated-radiotherapy (IMRT)- or volumetric-modulated-arc-therapy (VMAT)-based dose–volume parameters and 5-year outcome for a consecutive series of non-metastatic nasopharyngeal cancer (NPC) patients (pts) treated in a single institution in a non-endemic area in order to identify potential prognostic factors. Materials and methods: A retrospective analysis of consecutive non-metastatic NPC pts treated curatively with IMRT or VMAT and chemotherapy (CHT) between 2004 and 2014 was conducted. One patient was in stage I (0.7%), and 24 pts (17.5%) were in stage II, 38 pts (27.7%) in stage III, 29 pts (21.2%) in stage IVA, and 45 pts (32.8%) in stage IVB. Five pts (3.6%) received radiotherapy (RT) alone. Of the remaining 132 pts (96.4%), 30 pts (21.9%) received CHT concomitant to RT, and 102 pts (74.4%) were treated with induction CHT followed by RT-CHT. IMRT was given with standard fractionation at a total dose of 70 Gy. Clinical outcomes investigated in the study were local control (LC), disease-free survival (DFS), and overall survival (OS). Kaplan–Meier (KM) analysis was performed for the outcomes considering dose and coverage parameters, staging, and RT technique. Results: Overall, 137 pts were eligible for this retrospective analysis. With a median follow-up of 70 months (range 12–143), actuarial rates at 5 years were LC 90.4, DFS 77.2, and OS 82.8%. For this preliminary study, T stage was dichotomized as T1, T2, T3 vs. T4. At 5 years, the group T1–T2–T3 reported an LC of 93%, a DFS of 79%, and an OS of 88%, whereas T4 pts reported LC, DFS, and OS, respectively, of 56, 50, and 78%. Pts with V95% > 95.5% had better LC (p = 0.006). Pts with D99% > 63.8 Gy had better LC (p = 0.034) and OS (p = 0.005). The threshold value of 43.2 cm3 of GTVT was prognostic for LC (p = 0.016). To predict the risk of local recurrence at 5 years, we constructed a nomogram which combined GTVT with D99% relative to HRPTV. Conclusions: We demonstrated the prognostic value of some dose–volume parameters, although in a retrospective series, this is potentially useful to improve planning procedure. In addition, for the first time in a non-endemic area, a threshold value of GTVT, prognostic for LC, has been confirmed.